A lightweight traceable D2D authentication and key agreement scheme in 5G cellular networks. (October 2021) - Chow, Man Chun; Ma, Maode
Highlights: Lightweight authentication protocol for 5G device-to-device (D2D) networks. Support 5G network operators to trace and identify malicious free-riding mobile users. Short and fast message authentication with HMAC and elliptic curve cryptography. Anonymity protection with GUTI based on 3GPP 5G Core Network. Abstract: Device-to-device (D2D) communication is one of the promising features in 5G cellular networks. However, there are also new security challenges such as mutual authentication, device anonymity protection, end-to-end data secrecy, and free-riding attack prevention. Therefore, there is a need to develop an authentication scheme that addresses all these security concerns. The scheme must also be computationally lightweight, such that it supports all mobile devices having limited battery and computational resources. To overcome these challenges, in this paper, we propose a lightweight traceable D2D authentication and key agreement protocol (LT-AKA) based on the existing 3GPP 5G mobile networks. The LT-AKA scheme uses randomly generated hash-based message authentication code (HMAC) to guarantee message authorships, and Elliptic Curve Diffie-Hellman (ECDH) to facilitate secure key exchange. Security evaluation shows that our protocol is resilient to various network attacks including free-riding attacks. Performance evaluation shows that our protocol is 36.5%, 51.5%, and 7.7 times faster than the existing schemes. Graphical abstract: Image, graphical abstract